2021
DOI: 10.3389/fendo.2021.677912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Chinese Patients With Erythrodermic Psoriasis: A Case-Control Study

Abstract: Erythroderma psoriasis (EP) is a rare and severe form of psoriasis, which is a chronic inflammatory skin disease that usually occurs simultaneously with cardiovascular disease (CVD). Metabolic syndrome (MetS) is a significant precursor of CVD. This study was to investigate the association between EP and MetS in the Chinese population. We conducted a retrospective study on 86 consecutive patients with EP and 100 healthy controls from Huashan Hospital between 2013 and 2018. Demographic, biochemical parameters fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…All studies had an average age range between 35 and 53 years old, except one study in which children with an average age of 13 years old were under investigation 48 . Ninteen of 21 studies recorded that psoriasis patients are greatly more affected by MetS 29–32,35–49 . Howbeit, statistical analysis results, following the removal of adjusted variables in one study, were altered.…”
Section: Resultsmentioning
confidence: 99%
“…All studies had an average age range between 35 and 53 years old, except one study in which children with an average age of 13 years old were under investigation 48 . Ninteen of 21 studies recorded that psoriasis patients are greatly more affected by MetS 29–32,35–49 . Howbeit, statistical analysis results, following the removal of adjusted variables in one study, were altered.…”
Section: Resultsmentioning
confidence: 99%
“…This is in concordance with the low prevalence of generalized-erythrodermic PsO in clinical series, where it represents 1–6% of all PsO patients ( 6 ). In LC5 there was a male predominance and 31% of patients could be classified as having erythrodermic features, defined by skin involvement of at least 80–90% ( 7 ). The severity and extent of disease in this class, as well as the high rate of severe pruritus, the higher number of comorbidities and the longer disease duration could explain the reported higher number of previous systemic treatments, especially biologics, in this class compared with the others.…”
Section: Discussionmentioning
confidence: 99%
“…PsA, hypertension and kidney disease were remarkably more prevalent in LC5 compared with other classes. Arterial hypertension is known to be more prevalent in erythrodermic PsO ( 7 ). Comorbidities may be partially explained by lifestyle factors, such as drinking alcohol and smoking, that were more prevalent in patients with generalized erythrodermic PsO ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Interestingly, the study found no correlation between the severity of erythrodermic psoriasis and the prevalence of MetS. 61 A case-control study conducted in Thailand reported that there was no significant variation in the severity of psoriasis between the MetS group and the non-MetS group in Southeast Asia. 62 An increasing number of studies have substantiated that psoriasis is not merely an inflammation of the skin, but also affects the whole-body system.…”
mentioning
confidence: 96%